2015
DOI: 10.1007/s10336-015-1218-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that dorsally mounted satellite transmitters affect migration chronology of Northern Pintails

Abstract: We compared migration movements and chronology between Northern Pintails (Anas acuta) marked with dorsally mounted satellite transmitters and pintails marked only with tarsus rings. During weekly intervals of spring and autumn migration between their wintering area in Japan and nesting areas in Russia, the mean distance that ringed pintails had migrated was up to 1000 km farther than the mean distance radiomarked pintails migrated. Radiomarked pintails were detected at spring migration sites on average 9.9 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 31 publications
1
18
1
Order By: Relevance
“…While we find a delay in timing of reproduction and possibly timing of migration for birds with harness-attached transmitters, the delay is only minor, and other aspects of migration or reproduction are not affected. In contrast with earlier studies, which have shown strong negative effects on migration timing and reproduction for birds equipped with tracking devices [20,33,35], we find that tracking devices are reliable tools to study timing of migration and reproduction, and the modified harness which we have developed appears to be a reliable method to attach tracking devices on geese. Given our different results for different sexes, we stress that researchers make a careful consideration which birds they equip with tracking devices.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…While we find a delay in timing of reproduction and possibly timing of migration for birds with harness-attached transmitters, the delay is only minor, and other aspects of migration or reproduction are not affected. In contrast with earlier studies, which have shown strong negative effects on migration timing and reproduction for birds equipped with tracking devices [20,33,35], we find that tracking devices are reliable tools to study timing of migration and reproduction, and the modified harness which we have developed appears to be a reliable method to attach tracking devices on geese. Given our different results for different sexes, we stress that researchers make a careful consideration which birds they equip with tracking devices.…”
Section: Discussioncontrasting
confidence: 48%
“…Also, the migration speed of these birds was not affected. For comparison, an earlier study in northern pintails Anas acuta found that birds with harness-attached tracking devices arrived 19 days later on the breeding grounds in comparison with the population mean [20]. This is ascribed to a higher cost of migration, which is also suggested by models from Pennycuick et al [32].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This is supported by Bowlin et al [9] who show that backpack attached geolocators on stuffed Common Swifts Apus apus increased drag and thus their flight ranges. Similarly, Hupp et al [39] found that Northern Pintails equipped with 12-20 g satellite transmitters [1-3% of the bird's body weight (BBW)] in East Asia build up a delay of 7.7 days per 1000 km during their migration compared to birds that were only ringed. Higher energetic costs during flight are given as a likely explanation.…”
Section: Harness-attached Backpackmentioning
confidence: 98%
“…For larger birds, it is sometimes possible to equip a control group with lightweight (< 1 g) geolocators on the colour rings, which can be used to measure migration variables such as moment of departure and arrival, and migration speed ( [22], Lameris et al unpublished). Yet, ring resightings and recoveries can also give useful estimates for comparison of some migration variables [39], such as the moment of arrival [8]. Observing birds after release can reveal differences in behaviour and short-term survival between the tagged group and the control group.…”
Section: Towards Reduction In Adverse Effectsmentioning
confidence: 99%